Research protocol development: basic concepts for clinicians - Kumari, Archana; Sinha, Bipin; Ranjan, Piyush (International Journal of Research in Medical Sciences, 2017)
The research output from most of the teaching medical institutions of our country is dismal. Medical students and faculties can routinely contribute to the research publication by developing proper instinct and attitude. Research ideas are generated from interesting observations that one comes across during day to day clinical practice. Every research question should be assessed by FINER criteria. Methodical search of existing literature is extremely important. Research hypothesis should be written in PICOT format. Knowledge of biostatistics and collaboration with basic sciences and paraclinical specialties are keys to scientifically correct clinical research protocol development.